SIMULATION STUDY OF A STAND-ALONE PHOTOVOLTAIC ELECTRICITY GENERATION SYSTEM - SUNDERAN, PRASHANTHINI (2011)
The energy demand of the nation is growing rapidly as Malaysia thrusts forward towards becoming a developed nation. Generation of electricity is still heavily dependent on combustion of fossil fuels such as natural gas and coal. The emissions from the combustion of fossil fuels have led to serious environmental and climatic problems such as global warming and air pollution. The depleting nature of fossil fuels adds further constraint to the utilization of these fuels in meeting the nation’s future energy needs. The problems associated with fossil fuels initiated the interest to explore alternative energy sources that are more environmentally friendly and sustainable for electricity generation. Since Malaysia is located near the equator with monthly average daily solar irradiation of approximately 4500 Wh/m2 and average sunshine duration of up to 8 hours, the utilization of solar energy for electricity generation has great prospects. The photovoltaic-based electricity generation system (PVEGS) converts sunlight into electricity using photovoltaic (PV) modules. However, sunlight is not available continuously throughout the day.